TORAKOCHIRURGIAThe importance of immunohistochemistry for differentiation of lung adenocarcinoma and squamous cell carcinoma in small samples and cytology specimens - Langfort, Renata; Szołkowska, Małgorzata; Szczepulska-Wójcik, Ewa; Qandil, Naim; Maksymiuk, Beata; Giedronowicz, Dorota; Rudziński, Piotr; M. Orłowski, Tadeusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction : In many cases typing of advanced lung non-small cell carcinoma (NSCLC), especially differentiation between adenocarcinoma (ADC) and squamous cell carcinoma (SCC), requires special stains, mainly immunohistochemistry (IHC). Methods : 53 cases of NSCLC diagnosed on small biopsies and cell block samples were evaluated. The panel of IHC antibodies comprised markers characteristic for ADC (TTF-1, napsin A, CK7) and for SCC (p63, CK5/6, CK34ßE12) in order to determine their value in diagnosis of NSCLC. Besides IHC, mucicarmine stain was tested. Results were correlated with the final diagnosis obtained from surgical specimens. Results : In 57% of cases the subtype of NSCLC was established only by H+E stain. Using mucin stain and immunohistochemistry the accuracy of diagnosis increased by 22% to reach 79%. P63 turned out to be the most specific antibody, whose expression was seen in the vast majority of SQCC and in a squamous component of other types of NSCLC. CK5/6 exhibited similar specificity to p63 but was lower in sensitivity. TTF-1 and napsin A were the most useful antibodies for ADC and a positive reaction was seen in about 60% of ADC. Both markers were highly specific but, like p63, less sensitive. Since CK7 and CK34 proved less specific, their value in typing of NSCLC was limited. Mucin stain seemed to be a valuable marker but not very sensitive, although it was very helpful in diagnosis of TTF-1 negative ADC. Conclusions : IHC allows one to make a more accurate diagnosis than H+E stain alone. The most effective panel of IHC that facilitates subclassification of NSCLC in small samples and cell blocks comprised TTF-1, p63 and mucicarmine stain.